2021
DOI: 10.1021/acsami.0c20826
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vertical Inhomogeneity on the Charge Extraction in Perovskite Solar Cells: A Study by Depth-Dependent Photoluminescence

Abstract: In perovskite solar cells (PSCs), the vertical inhomogeneities which include uneven grains, voids, and grain boundaries are closely linked to the underlying charge transport layer which controls the nucleation and grain growth in the perovskite film. Herein, the vertical inhomogeneity of perovskite films in the device structure is analyzed by depth-dependent photoluminescence (PL) achieved with different excitation wavelengths. An analytical representation between vertical inhomogeneity and depth-dependent PL,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 74 publications
(126 reference statements)
0
17
0
Order By: Relevance
“…[34][35][36] As shown in Figure 2e, the front PL peak (979 nm) shows a clear red shift in comparison with the back PL peak (976 nm). Because a 360 nm excitation laser was used in the PL measurement, the penetrate depth in the perovskite film is only ≈50 nm, [37] so the peak shift can reflect different perovskite compositions on the top and bottom surfaces, respectively. The uneven metal element distribution along the vertical direction could be ascribed to the different crystallization dynamics between Sn-and Pb-based perovskites.…”
Section: Resultsmentioning
confidence: 99%
“…[34][35][36] As shown in Figure 2e, the front PL peak (979 nm) shows a clear red shift in comparison with the back PL peak (976 nm). Because a 360 nm excitation laser was used in the PL measurement, the penetrate depth in the perovskite film is only ≈50 nm, [37] so the peak shift can reflect different perovskite compositions on the top and bottom surfaces, respectively. The uneven metal element distribution along the vertical direction could be ascribed to the different crystallization dynamics between Sn-and Pb-based perovskites.…”
Section: Resultsmentioning
confidence: 99%
“…The 7 keV X-rays penetrate through all perovskite layer while the UV-LED probes less than 50 nm. [37,43] Consequently, UV-LED emission originates from the surface and is more sensitive to environmental conditions, while X-ray probes the bulk. For instance, if the inner layers of the material had a more significant Br content, with I segregated to the surface, that would cause a redshift in the PL emission.…”
Section: Discussionmentioning
confidence: 99%
“…Further, simple analyses to include the real device characteristics were performed comparing the PL quenching between OC and SC conditions. [21,[26][27][28] In particular, Du et al [21] found a linear relationship between the logarithm of the PL quenching and the power conversion efficiency (PCE) or the V oc . This linear relationship was found by analyzing three devices containing the same absorbing layer.…”
Section: Introductionmentioning
confidence: 99%